Trabalho, moradia e cidade : lutas de trabalhadores no Pouso Frio de Toledo (décadas de 1950-1990) - Pereira, Maria Cristina de Castro (2016)
This paper discusses the historical process of transformation in rural capitalist production which imposed limits on the length of different subjects in the field. While many sought other regions where family farms were still possible, others have moved to nearby cities, looking for land or cheap rents, often located in neighborhoods devoid of any infrastructure. Work possibilities also not allowed best expectations. Faced with all these difficulties, in Toledo, Cold Pouso and the factory is constituted as spaces of struggle and resistance mainly in the 1970s to 1990. Fighting for public services in the district and for better working conditions. In this process, building networks of solidarity among family, friends and neighbors contributed significantly to the organization of confrontation. This work tries to precisely understand the dynamics of construction of these social processes and movements of workers in the city of Toledo that period. The call occupying area of Frio Pouso in the city of Toledo / PR, in the decades of 1970-90, was the scene of conflicts and movements, among other implications, caused the removal of dozens of families to other areas of the neighborhood and the city. The so-called "regularization" of this area was accompanied, among other things, the realignment, widening and opening streets; realignment of fences and walls; drainage of wetlands and retreat and transport of house areas. These projects were designed and implemented without the consultation of workers Frio Pouso and without actually take real commitment to improving the living conditions of these subjects. To guide research for the establishment of the Cold Pouso and the changes produced in this space, privilege the questioning of the experiences of individuals who lived in this area: their survival strategies; integration into the labor market; problems faced; housing conditions; expectations; social practices produced struggle; and finally, making the interpretation of this present process